Current Approaches for Engaging Parents in Students’ Academic Performance: Basis for Parental Engagement Policy (American Journal of Multidisciplinary Research and Innovation, 2023)
This action research aims to determine the current approaches that the school has employed to enhancing parental engagement on the academic performance of the students in the new normal. The participants were of the selected 35 high school teacher, which contains 21 Junior High School teachers and 14 Senior High School teacher, from Valeriano E Fugoso Memorial High School at Boys Town Complex Parang, Marikina City. Parental engagement at school approaches includes volunteering, conferencing with teachers, attending workshops, involvement at school decision making. Also, the parental engagement in the student’s education at home approaches includes helping on homework, communicating encouragement and educational expectation. Results displayed that these approaches enabled parental engagement. Mostly, optimistic comment information from the parents were stimulated and promoted better insight of their child’s performance in school. A significant effect on the academic performance of the learner in PreCalculus course towards the engagement of the parents, whether at home or at school in the new normal. Similarly, parents became more involved both at home and school activities because of the effect of the several approaches which have improved performance in PreCalculus.